Policy Implementation and Evaluation Career Development Of Functional Officials In Improving Organizational Performance Within The Police Stamarena - Arthur Josias Simon Runturambi; Bagus Panuntun (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study explores career development policy implementation and evaluation for functional officials at Stamarena Police, focusing on enhancing organizational performance. Career development within organizations, particularly law enforcement agencies, plays a crucial role in improving employee performance and professional service delivery. Using a qualitative methodology with a literature review approach, the research analyzed policy documents, performance reports, and relevant scientific publications concerning police career development and human resource management. The findings identified several key challenges, including suboptimal competency-based performance evaluation systems, limited professional growth opportunities, and inadequate integration of career management information systems within Stamarena Police. The study reveals the necessity for strengthened planning and budgeting strategies to support sustainable career development initiatives. Recommendations include enhancing performance assessment mechanisms, expanding competency development programs, and integrating information systems to optimize career management for functional officials at Stamarena Police. These findings contribute to the broader understanding of career development in law enforcement institutions and provide practical solutions for improving organizational effectiveness.